Headhunters [videorecording (DVD)] - Tyldum, Morten; Hennie, Aksel, 1975-; Coster-Waldau, Nikolaj, 1970-; Lund, Synnøve Macody, 1976-; Nesbø, Jo, 1960- (Magnolia Home Entertainment, 2012)
A successful headhunter subsidizes his expensive lifestyle by stealing valuable artwork, but when he meets a former mercenary his two professional worlds collide.